Feasibility Study of Crushing Plant Location at Quarry Andesite, West Java, Indonesia, using Rock Mass Classification and Kinematic Analysis. (April 2018) - Azzam, M A; Rinaldi, M; Wibowo, S; Zakaria, Z; Muslim, D; Mulyo, A
Abstract: In engineering of open pit mine, safety is the most basic thing to be focused on, especially the slopes in the mining area. Hence, characteristic of rock slopes need to be determined precisely and accurately to identify the stability of the slopes. This study is done in andesite quarry slope in Jelekong, Bandung District, West Java, Indonesia, which is the location of crushing plant construction by Widaka Indonesia Inc. The purpose of this research is to determine the mass characteristic of andesite quarry slope in order to know the slope feasibility level as a construction location of crushing plant. The method used to determine the mass characteristic is by identifying the rock mass based on RMR (Rock Mass Rating) by Binieawski (1989) and also the type of failure, which could potentially happen based on kinematics analysis. The slope condition is analyzed based on field investigation and laboratory test results. RMR value shows that the rock mass is between 63-78, which is included into class II (Good Rock). Kinematics analysis also gives result that the rock slope will not have a failure or in other words, in a stable condition. Based on the research results, the location is suitable to construct a crushing plant.